Study on clinical profile and management of varicose veins of lower limbs - Kumar, Gorijavolu Naveen; Dattatreya, C. V. N. M.; Naik, M. Krishna (International Surgery Journal, 2019)
Background: The venous system of the lower limbs has the burden of posture, and blood has to be forced to the heart chamber against gravity. Commonly this problem is tackled either by a conservative approach or by surgical interference, both of which have their limitations. In the present study, an attempt is being made to study various clinical presentations of varicose veins, their management and complications. Methods: The data for the study was obtained from the patients admitted and treated in Tertiary Care Hospital, Kurnool for a period of two years from November, 2015 to November, 2017. Patients presenting with signs and symptoms of varicose veins, who were diagnosed as having varicosities of the superficial veins by clinical examination, were taken up for the study, after explaining the nature of the disease and various modalities of treatment available. Results: It is found that varicose veins and their associated symptoms and complications constitute the most common chronic vascular disorders leading to surgical treatment. It is more common in middle-aged group and in males. Patients presented with spectrum of symptoms and signs, dilated and tortuous veins being more common presentations. Long saphenous system is the most common venous system affected. Conclusions: Complications are negligible if cases are meticulously selected and operated. The present procedures enable the patient to lead almost normal life after surgery and the morbidity rate is very negligible. Though the newer trends in the management of varicose veins are showing good results, they need a long term follow up.